The Consequences of Social Policy for Subjective Well-Being: A New Paradox? - Naoki Akaeda (Luxembourg Income Study (LIS), 2022)
The present study uses benefit recipiency data and three dimensions of welfare transfers, namely, transfer share, low-income targeting, and universalism, to clarify the more detailed effects of social policies on subjective well-being and well-being inequality. This analysis utilizes benefit recipiency data from the Luxembourg Income Study Database, pooled data from the World Values Survey from 1981 to 2022, and a two-way fixed-effects model to explore the effects of these three dimensions of welfare transfers on life satisfaction and of the cross-level interactions of the welfare transfer variables and household income on life satisfaction. The results of this study indicate that (1) transfer share is positively associated with life satisfaction and (2) lowincome targeting shortens the well-being inequality stemming from income but at the cost of life satisfaction among rich individuals.
Keywords: 330; welfare transfers; subjective well-being; well-being inequality; World Values Survey; cross-level interaction; two-way fixed-effects model